Handbook of self-regulation : research, theory, and applications - Vohs, Kathleen D.; Baumeister, Roy F., 1953- (The Guilford Press, 2016)
"This authoritative handbook reviews the breadth of current knowledge on the conscious and nonconscious processes by which people regulate their thoughts, emotions, attention, behavior, and impulses. Individual differences in self-regulatory capacities are explored, as are developmental pathways. The volume examines how self-regulation shapes, and is shaped by, social relationships. Failures of self-regulation are also addressed, in chapters on addictions, overeating, compulsive spending, and attention-deficit/hyperactivity disorder. Wherever possible, contributors identify implications of the research for helping people enhance their self-regulatory capacities and pursue desired goals"--Resumé vydavatele